2014
DOI: 10.1088/0953-4075/47/9/095001
|View full text |Cite
|
Sign up to set email alerts
|

State-insensitive dichromatic optical-dipole trap for rubidium atoms: calculation and the dicromatic laser's realization

Abstract: Magic wavelength optical-dipole trap (ODT) allows confinement of neutral atoms and cancellation of the position-dependent spatially inhomogeneous differential light shift for a desired atomic transition. The light shift of the 87Rb 5P3/2 state can be expediently tailored to be equal to that of the 87Rb 5S1/2 state by employing dicromatic (λ1 + λ2 (here λ2 = 2λ1 ∼ 1.5 µm)) linearly polarized ODT lasers. In our calculation, two sets of state-insensitive dichromatic (784.3 + 1568.6 nm and 806.4 + 1612.8 nm) are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The trapping laser repopulates atoms into both ground states via scattering through D1 transition, however, this effect is slow and any population that does decay to dark ground state during the loading process is pumped with a re-pump laser back to |g prior to interrogation. The steady-state absorption of this four-level atomic system is modelled using the density matrix, ρ, which is governed by the Liouville equations [31,32] of the general form:…”
Section: Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…The trapping laser repopulates atoms into both ground states via scattering through D1 transition, however, this effect is slow and any population that does decay to dark ground state during the loading process is pumped with a re-pump laser back to |g prior to interrogation. The steady-state absorption of this four-level atomic system is modelled using the density matrix, ρ, which is governed by the Liouville equations [31,32] of the general form:…”
Section: Modellingmentioning
confidence: 99%
“…In other circumstances, it has been suggested that bichromatic traps might offer a solution [27][28][29]. Indeed, some calculated possibilities for Rb and Cs have been published [28][29][30]. Nonetheless, to our knowledge no-one has yet demonstrated a bichromatic magic trap for an optical transition.…”
Section: Introductionmentioning
confidence: 97%
“…Thus the transition frequency between the ground and the excited states are shifted. Taking the multilevel structure of the atom into account, the light shift for the atoms in a linearly polarized ODT is given by [18,25,26]:…”
Section: Experiments Results and Discussionmentioning
confidence: 99%
“…The calculation of the polarizability of 6S 1/2 state is similar to Ref. [23]. The dynamic polarizability of the 43S 1/2 state is given by The positions of the 43S 1/2 ↔ nP transitions are indicated by the arrow lines together with the corresponding nP labels in Fig.…”
Section: Magic Odt For Ground-state and Rydberg-state Cs Atomsmentioning
confidence: 97%
“…[20] and experimentally demonstrated in strong-coupling cavity quantum electrodynamics system [21] for applications in quantum measurement and precision metrology [22]. Previous studies on the magic-wavelength ODT of neutral atoms mainly focus on the transition from ground state to a low-excited state [21][22][23][24][25][26]. In 2005, a blue-detuned magic-wavelength bottle beam trap was proposed for trapping the 5S 1/2 ground state and 50D 5/2 Rydberg state of Rb atoms [27], and recently Barredo et al experimentally demonstrated the bottle beam trap for Rydberg-state Rb atoms [18].…”
Section: Introductionmentioning
confidence: 99%